PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN OUTSOURCING PT. GAPURA ANGKASA DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Yuni Purnawati (CV. Multi Kreasi Media, 2022)
Compensation and work discipline are factors that influence employee performance. Facts in the field the company still has not provided proper compensation to its employees and employees have not complied with company rules so that it can affect employee performance. This study aims to determine the effect of compensation and work discipline on the performance of outsourced employees of PT. Gapura Angkasa at Zainuddin Abdul Madjid International Airport Lombok. This study uses quantitative research methods with sampling techniques using saturated samples, data obtained by distributing questionnaires to outsourced employees of PT. Gapura Angkasa at Zainuddin Abdul Madjid International Airport Lombok, Respondents in this study totaled 47 Outsourcing employees. Data analysis using multiple linear regression test, t test, and f test. The results of this study indicate that (1) employee compensation have a significant effect on the performance of outsourced (2) employee work discipline have a significant effect on the performance of outsourced (3) Simultaneously compensation and employee work discipline have a significant effect on the performance of outsourced Gapura Angkasa at Zainuddin Abdul Madjid International Airport, Lombok.